Management Implications for Skates and Rays Based on Analysis of Life History Parameters - Liu, Kwang-Ming; Huang, Ya-Wen; Hsu, Hua-Hsun (Frontiers in Marine Science, 2021)
The life history (age and growth and reproduction) parameters of 35 species (41 stocks) of skates and rays were analyzed using multivariate analyses. Three groups were categorized by cluster analysis (CA) based on principal component scores. Empirical equation was developed for each group to describe the relationships between the predicted a finite rate of population increase (λ′) and the life history parameters: growth coefficient (k), asymptotic length (L∞), age at maturity (Tm), annual fecundity (f/Rc), ratio between size at birth (Lb), and L∞ (Lb/L∞), and ratio between size at maturity (Lm) and L∞ (Lm/L∞). Group 1 included species with slow growth rates (k < 0.011 year–1), early maturity (Lm/L∞ < 0.62), and extended longevity (Tmax > 25 years); Group 2 included species with intermediate growth rates (0.080 year–1 < k < 0.190 year–1), intermediate longevity (17 years < Tmax < 35 years), and late maturity (Lm/L∞ > 0.60); Group 3 included species with a fast growth rate (k > 0.160 year–1), short longevity (Tmax < 23 years), and large size at birth (Lb/L∞ > 0.18). The λ′ values estimated by these empirical equations showed good agreement with those calculated using conventional demographic analysis, suggesting that this approach can be applied in the implementation of management measures for data-limited skates and rays in a precautionary manner.